Revitalisasi Kurikulum Pendidikan Agama Islam: Upaya Meningkatkan Religiusitas Siswa SMK - Aklima; Prasetyo, Muhammad Anggung Manumanoso; Yusrianti, Susi (JoIEM (Journal of Islamic Education Management), 2025)
The religious aspect served as a fundamental foundation in developing students' character. In this context, educational institutions played a critical role in character formation by systematically integrating the curriculum. This study was significant as it formulated a curriculum model that enhanced religiosity within vocational schools. The study employed a qualitative research approach and utilized descriptive survey techniques. The primary informants included the school principal, the vice principal of curriculum, and the coordinator of religious activities. Informant selection was conducted using snowball sampling methodology. The research findings indicated that curriculum management implementation was achieved through optimizing managerial functions, spanning from the planning phase to evaluation. Policies were operationalized through workshops, subjects aligned with teachers' competencies, and structured evaluations of students' performance. The proposed curriculum achievement model emphasized cultivating students' religiosity through religiously oriented extracurricular activities, assessed through practical evaluations. Monitoring the enhancement of students' religiosity was evidenced by observable changes in student behavior and improvements in examination results in religious studies.